Pengaruh Pendapatan Per Kapita, Jumlah Penduduk dan Jumlah Kendaraan Bermotor Terhadap Konsumsi Bahan Bakar Minyak Pertalite dan Pertamax di Provinsi Sumatera Barat - Sukma, Tri; Ariusni (Universitas Negeri Padang, 2024)
By 2022, consumption of RON 90 fuel in Indonesia will reach 29.68 million liters, up 27% from 23.3 million liters in the previous year, as transportation and industrial activities increase. Fuel in Indonesia is sold in various brands such as RON 90, RON 92, and RON 95. The increase in RON 90 fuel consumption is significant in several regions, including West Sumatra which has 19 regencies/cities. The use of renewable energy in West Sumatra is increasing rapidly, reaching 29% by 2022. Despite the high potential of renewable energy, oil energy consumption remains large and continues to increase. This study aims to see the effect of per capita income, population, and motorized vehicles on Pertalite and Pertamax fuel consumption in West Sumatra. The results of panel data regression analysis show that income per capita has a significant positive effect on Pertalite consumption, but positive and insignificant for Pertamax. Total population has a significant positive effect on Pertalite and Pertamax consumption. The number of motorized vehicles has a positive and insignificant effect on Pertalite consumption, but is significantly positive for Pertamax.